Evaluasi Pelaksanaan Akuntabilitas Pada Yayasan XYZ - Jessica Vianto; Dodik Siswantoro (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to evaluate the practice of accountability at the XYZ Foundation. XYZ Foundation is a non-profit organization that is still developing so it needs stakeholder support to achieve the vision and mission of the organization. In getting this support, the XYZ Foundation needs to carry out accountability to gain public support. Methodology/approach: This study evaluates financial accountability based on ISAK 35 and evaluates performance accountability based on financial ratios. Researchers also conducted a comparative analysis to get the best practices from similar organizations. The research method used is descriptive qualitative with a case study approach and researchers collect primary and secondary data through interviews, documentation and collect digital documentation published by XYZ Foundation through social media and official websites. Findings: The results showed that accountability has not been performed optimally by XYZ Foundation. Through comparative analysis, XYZ Foundation can identify best practices from similar organizations. Practical and Theoretical contribution/Originality: This research evaluates accountability practices with the approach of performance and financial indicators of XYZ Foundation and conducts a comparative analysis with similar organizations. Research Limitation: This research was only conducted on one entity, namely the XYZ Foundation with the period 2020-2022.